The Influence of Labor Force Participation and Education on Gender Development in South Sulawesi Province in 2006-2022 - Lestari, Umi (ICOR: Journal of Regional Economics, 2024)
This study aims to determine the eect of male labor force participation rate, female labor force participation, male education and female education on gender development index in South Sulawesi Province in 2006-2022. The method used in this research uses secondary data and data analysis usung multiple linear regression with eviews 12. The result showed that the male labor force participation has no effect on the gender development index. Labor force participation has no effect on the gender development index. Male education has a significant effect on the gender development index, this means that with the increase in education in a region, the gender development index in the area will also increase.